Discovery Learning Model Assisted by Serial Pictures: It’s Effect on Short Story Writing Ability of PGSD Students - Buaga, Garib Firman; Wuryandani, Wuri; Nugroho, Ikhlasul Ardi; Kartono; Kevin Alvianto (Universitas Pendidikan Ganesha, 2024)
The problem of students' short story writing skills is still a challenge in learning at the higher education level. Conventional learning that is limited to understanding theory is considered less effective in improving students' practical skills. This study aims to analyze the effect of discovery learning model assisted by serialized picture media on improving students' short story writing skills. The research used quantitative methods with a pseudo-experimental design and non-equivalent control group design. The sample was taken by random sampling, with one class as the control group and one class as the experimental group. Data were collected through essay tests and analyzed using t-test. The results of the analysis showed that the value of Tcount = 3.623, this value was then compared with Ttable at the 5% significance level (α = 0.05) with dk (35 + 32-2 = 65). So that the value of Ttable = 2.500 is obtained. Because the value of Tcount = 3.623 > Ttable 2.500, Ho is rejected, indicating a significant difference between the experimental and control groups. In conclusion, the discovery learning model assisted by serialized picture media has a significant effect on improving students' short story writing skills compared to conventional learning.